Decreased SPTLC1 expression predicts worse outcomes in ccRCC patients - Zhu, Wen‐Kai; Xu, Wen‐Hao; Wang, Jun; Huang, Yong‐Qiang; Abudurexiti, Mierxiati; Qu, Yuan‐Yuan; Zhu, Yi‐Ping; Zhang, Hai‐Liang; Ye, Ding‐Wei (Journal of cellular biochemistry, 2020)
Objective Serine palmitoyltransferase, long chain base subunit 1 (SPTLC1) catalyzes the first step in sphingolipid synthesis and has been implicated in the progression of various cancers. However, its role in clear cell renal cell carcinoma (ccRCC) remains unclear. Here, we investigated the expression and prognostic value of SPTLC1 in ccRCC. Methods Three ccRCC patient cohorts were studied. ccRCC and adjacent normal kidney tissue samples were obtained from 183 patients at the Fudan University Shanghai Cancer Center (FUSCC) and subjected to immunohistochemical staining and quantitative reverse‐transcription polymerase chain reaction to evaluate SPTLC1 protein and messenger RNA (mRNA) expression. Two validation cohorts consisting of mRNA and clinicopathological data sets from patients with ccRCC were obtained from the Cancer Genome Atlas (TCGA, n = 429) and Oncomine (n = 178) databases. Associations between low and high SPTLC1 mRNA and protein expression and survival were evaluated using the Kaplan‐Meier method and log‐rank test. Independent prognostic factors were identified using univariate and multivariate Cox regression analysis. Results SPTLC1 mRNA or protein were expressed at significantly lower levels in ccRCC tissues compared with normal kidney tissues in all three patient cohorts (P < .001). Low SPTLC1 expression was significantly associated with shorter overall survival in the FUSCC (P = .041) and Oncomine (P < .001) cohorts, and was significantly associated with shorter overall survival (P < .0001) and progression‐free survival (P < .001) in the TCGA cohort. Bioinformatics analysis identified 10 genes significantly coregulated with SPTLC1 in ccRCC, most of which contributed to sphingomyelin metabolism (SPTLC2, SPTLC3, SPTSSA, SPTSSB, ORMDL1, ORMDL2, ORMDL3, ZDHHC9, GOLGA7B, and KDSR). Functional enrichment analysis predicted that SPTLC1 and its network play significant roles in inflammatory, hypoxia, and interferon gamma responses, and in allograft rejection pathways. Conclusion Low SPTLC1 expression is significantly associated with disease progression and poor survival in patients with ccRCC, suggesting that SPTLC1 may function as a tumor suppressor. Thus, SPTLC1 could be a potential new biomarker and/or therapeutic target for ccRCC. Serine palmitoyltransferase, long chain base subunit 1 (SPTLC1) involves in sphingolipid metabolism pathway and suppresses the progression of various tumors. However, the role of SPTLC1 in clear cell renal cell carcinoma (ccRCC) remains unclear. This study aims to identify the expression of SPTLC1 in ccRCC and clarify its prognostic value in patients with ccRCC.